Letter - Rodríguez Vega, José
012a-0039-001 Union General de Trabajadores de España COMITÉ NACIONAL October 21st, 1938 Comrade HALLSWORTH President of the Trades Union Congress London. Dear Comrade, We wish to send you our brotherly greetings for your election to the chairmanship of the T.U.C., and to express our satisfaction that at this hour of trial you may give thus the benefit of your experience and able leadership for the good of our common cause. Our good friend and comrade Léon JOUHAUX will explain to you why we would like to take advantage of the fact that representatives of our Organization will come to France early in November, to attend the National Congress of the C.G.T., for arranging a meeting with you in London a few days before. We feel that it might be of practical interest to be able to discuss with you at full length all practical matters related with the aid so much needed by our country, especially by our civil population. As the C.G.T. Conference takes place on November 14th, we venture to suggest that our visit might take place a few days earlier, within the preceding week. We shall very much esteem an early answer to let us know your opinion on this matter, and meanwhile we remain, with comradely greetings Yours for the Cause, BARCELONA On behalf of the Executive committee of the U.G.T. José Rodriguez Vega General Secretary. AVDA. DEL 14 DE ABRIL. 373 TELÉFS. 78878 y 79598 292/946/12a/39